The Effectiveness of Compressing Leaves (Erythrina Lithosperma) in Reducing Body Temperature in Toddlers at the Bojonegara Health Center - Saukiyatunnufus; Omega DR Tahun (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
Is a condition where the body temperature is higher than normal, namely 38 degrees Celsius, which is caused by a body condition that creates more heat than is released. Fever in children is one of the most common clinical symptoms. As is well known, Dadap Serep Leaf compress (Erythrina lithosperma) is believed to be a non-pharmacological therapy to treat fever due to this infection, although not many studies have explained its effectiveness. Was carried out by bivariate test analysis, first the normality test was carried out with the pretest and posttest design measurements. The sampling technique uses the expert validity test. Data analysis used the Kolmogorov-Smirnova and Shapiro Wilk tests. to determine the effect of compressing dadap serep leaves on decreasing body temperature levels in toddlers in the Bojonegara Health Center with 30 respondents. Of the study obtained a p value of 0.000 ≤ 0.05 from these results there was an effect of compressing dadap serep leaves on body temperature levels in toddlers at the Bojonegara Health Center.